2006
DOI: 10.1007/s00223-006-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Vitamin D Metabolites and Bone Mineral Density in Young Males: A Cross-Sectional and Longitudinal Study

Abstract: The purpose of this study was to investigate the association between vitamin D analogs and peak bone mineral density (BMD, g/cm(2)) in young men. The cohort consisted of 78 healthy young males with a mean age of 22.6 years at baseline. BMD of the total body, hip, and spine and lean body mass were measured at baseline and at follow-up 2 years later. Blood samples were assayed for 25-hydroxyvitamin D(2) (25OHD(2)), 25-hydroxyvitamin D(3) (25OHD(3)), and 25-hydroxyvitamin D (25OHD) at baseline using high-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…In a recent study (19), we found a strong relationship between levels of vitamin D and BMD in the same cohort as in the present study. These results are of interest also with respect to the present study, since vitamin A has been suggested to antagonize vitamin D's positive influence on bone mineralization and calcium uptake (23,(36)(37)(38).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In a recent study (19), we found a strong relationship between levels of vitamin D and BMD in the same cohort as in the present study. These results are of interest also with respect to the present study, since vitamin A has been suggested to antagonize vitamin D's positive influence on bone mineralization and calcium uptake (23,(36)(37)(38).…”
Section: Discussionsupporting
confidence: 87%
“…RBP-4 also showed a strong association with retinol (rZ0.61, P!0.001, data not shown). Levels of vitamin D 3 , presented in a previous paper (19) were not related to levels of retinol (rZK0.12, PO0.05), RBP-4 (rZK0.05, PO0.05), abdominal fat mass (rZK0.20, PO0.05), or weight (rZ0.02, PO0.05).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…We found no relationship between BMD and the serum 25(OH)D level. Some (6,7,9,17,21,34), but not all (18,19,22,25,35), studies have reported a significant association between the serum 25(OH)D level and BMD. A meta-analysis of randomized trials of vitamin D supplements in adults suggested reasonable evidence of an association between the serum 25(OH)D level and BMD predominantly in elderly women (36).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D and calcium intake contribute to bone mineral accrual during growth (25,26). By contrast, in adult men, current vitamin D status is weakly correlated with BMD (15,27,28). In young and middle-aged men, 25OHD was weakly correlated positively with BMD at the lumbar spine and the hip (13).…”
Section: Discussionmentioning
confidence: 99%